Method for preparing porous titanium by taking electrolytic pure titanium as raw material
By using electrolytic pure titanium to prepare porous titanium, and using molding and sintering processes, the problem of using pore-forming agents in the prior art is solved, and a simplified process and high porosity porous titanium preparation is achieved.
Patent Information
- Application Number
- CN202411867582.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-28
AI Technical Summary
In the existing porous titanium preparation methods, the use of pore-forming agents needs to solve problems such as uniformity, selection of pore-forming agent types and complex post-treatment processes, resulting in complex preparation processes and inconsistent performance.
Electrolytic pure titanium is used as raw material, and particles with particle sizes of 74-833 μm are obtained through crushing and sieving, and porous titanium with bimodal pore size distribution is directly prepared, avoiding the use of pore-forming agents.
The preparation process is simplified, and the porosity controllability is achieved, and porous titanium with bimodal pore size distribution characteristics is directly obtained, with high porosity and consistent performance.
Smart Images

Figure HDA0005194839530000011 
Figure HDA0005194839530000012 
Figure HDA0005194839530000013
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of porous titanium preparation, and in particular relates to a method for preparing porous titanium by taking electrolytic pure titanium as raw material. Background Art
[0002] Porous titanium is an excellent functional material that integrates many excellent properties. Due to its unique physical properties and the excellent chemical properties of titanium, it is widely used in chemical separation, biomimetics, aerospace, and marine engineering.
[0003] There are many methods for preparing porous titanium, usually powder metallurgy, additive manufacturing, chemical synthesis, liquid solidification, etc. Powder metallurgy is a method that has been reported more frequently and has a certain industrial scale in the field of preparing porous materials.
[0004] The specific raw material types for preparing porous titanium using powder metallurgy technology include hydrogenated dehydrogenated titanium powder, hydrogenated titanium powder, spherical titanium powder, etc. In many published reports on the preparation of porous titanium, due to differences in raw material properties and different requirements for process control, the prepared porous titanium also has different properties, and the final applicable application fields are also different.
[0005] Porous materials with bimodal or multimodal pore size distribution have the characteristics of two peaks or more peaks on the pore size distribution curve. Such porous materials have the characteristics of high porosity, wide pore size distribution, low density, etc. Due to the unique pore structure characteristics, they have good barrier, absorption and filtration properties, and have good application performance in energy absorption, heat insulation, electromagnetic field shielding, and biomedicine.
[0006] When using hydrogenated dehydrogenated titanium powder or spherical titanium powder as raw material, in order to obtain porous titanium with a bimodal or multimodal pore size distribution, it is necessary to use pore-forming agents with different particle size distributions to fill between the raw material powder particles, use a space-occupying method to perform pressing and molding, and then remove the pore-forming agent to obtain a blank with a multi-gradient pore size distribution, and finally sinter to obtain the finished product.
[0007] When using the pore-forming agent method (space-occupying method) to prepare porous titanium, the following problems need to be solved: ① The uniformity of the pore-forming agent. The pore-forming agent is added to the matrix powder and is difficult to mix evenly with the matrix powder. The unevenness of the space-occupying pore-forming agent in the matrix material will cause the spatial distribution of the final pores in the material to be uneven, resulting in inconsistent local performance of the material. ② The type of pore-forming agent has high requirements. The physical and chemical properties of the pore-forming agent will affect the preparation process of the porous material and the final performance of the product. Therefore, the general selection principle is that it does not react with the matrix material, is easy to remove, and is harmless. Therefore, there are fewer types of pore-forming agents that can meet the above requirements. Scholars have been continuously conducting research in this area. ③ The post-processing process is complicated. The use of solution leaching, high-temperature volatilization and other methods will increase the process steps and complexity, and the residue of the pore-forming agent will cause contamination of the matrix material and affect the material performance.
[0008] In short, under the existing technical conditions, the process from metal titanium powder to the final porous titanium product is still multi-step and multi-process, and there are still many problems that need to be optimized. Summary of the invention
[0009] In view of this, the purpose of the present invention is to provide a method for preparing porous titanium using electrolytic pure titanium as raw material. The method is simple, has a short preparation process, and has controllable porosity. It does not require the use of pore-forming agents and can directly obtain porous titanium with a bimodal pore size distribution characteristic.
[0010] The present invention provides a method for preparing porous titanium by using electrolytic pure titanium as raw material, comprising the following steps:
[0011] The electrolytic titanium is crushed and sieved to obtain particles with a particle size of 74 to 833 μm;
[0012] Pressing the particles with a particle size of 74 to 833 μm into a blank;
[0013] The blank is sintered to obtain porous titanium.
[0014] Preferably, the compression molding pressure is 50-190 MPa.
[0015] Preferably, the sintering temperature is 950-1300°C.
[0016] Preferably, the sintering is performed under an argon atmosphere.
[0017] Preferably, the sintering is performed by reduced pressure sintering with an absolute pressure less than 1 Pa.
[0018] Preferably, the electrolytic titanium has a purity greater than 99% of pure titanium, and is an aggregate formed by fine particles with a particle size ranging from 0.5 to 13 μm connected and grown together.
[0019] Preferably, the porous titanium has a bimodal pore size distribution.
[0020] The present invention provides a method for preparing porous titanium using electrolytic pure titanium as raw material, comprising the following steps: crushing the electrolytic titanium and then screening it to obtain particles with a particle size of 74 to 833 μm; molding the particles with a particle size of 74 to 833 μm to obtain a blank; sintering the blank to obtain porous titanium. The present invention uses metallic pure titanium obtained by molten salt electrolysis as raw material, and directly prepares porous titanium by molding-sintering, avoiding the cumbersome steps of pore-forming agent filling molding and then removing the pore-forming agent, greatly shortening the process; when the particles with a particle size of 74 to 833 μm are molded, the bridges between the particles can form a large pore space with a larger pore size, and the particles with a particle size of 74 to 833 μm are aggregates formed by connecting and growing together fine particles with a particle size range of 0.5 to 13 μm, which themselves have pores with a pore size range of 1 to 8 μm, so the prepared porous titanium has a bimodal pore size distribution and a high porosity. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 A schematic diagram of an embodiment of a method for preparing porous titanium using cathode precipitates of electrolytic titanium as raw materials provided by the present invention;
[0022] Figure 2 The macroscopic and microscopic morphologies of the electrolytic titanium used in Examples 1 and 2 of the present invention after crushing and screening;
[0023] Figure 3 The pore characteristics and pore size distribution of the porous titanium prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0024] The present invention provides a method for preparing porous titanium by using electrolytic pure titanium as raw material, comprising the following steps:
[0025] The electrolytic titanium is crushed and sieved to obtain particles with a particle size of 74 to 833 μm;
[0026] Pressing the particles of 74 to 833 μm into a shape to obtain a blank;
[0027] The blank is sintered to obtain porous titanium.
[0028] The method provided by the present invention is simple, has a short preparation process, and has controllable porosity. In addition, porous titanium with a bimodal pore size distribution characteristic can be directly obtained without using a pore-forming agent.
[0029] The present invention crushes and sieves the electrolytic titanium to obtain particles with a particle size of 74 to 833 μm. The electrolytic titanium used in the present invention is prepared by molten salt electrolytic titanium extraction or electrolytic refining process, with a purity of >99%. It is a large aggregate formed by "connecting" and growing together fine particles with a particle size range of 0.5 to 13 μm, and has secondary particle characteristics. The primary particles are not simply in contact or agglomerated, but are connected by growth and have a certain strength. In a specific embodiment, the particles after crushing and screening are electrolytic titanium particles of 365 to 833 μm or electrolytic titanium particles of 74 to 104 μm.
[0030] Figure 1 A schematic diagram of an embodiment of a method for preparing porous titanium using cathode precipitate of electrolytic titanium as raw material provided by the present invention; the electrolytic titanium is physically crushed and sieved to obtain electrolytic titanium particles; the electrolytic titanium is pure titanium with a purity greater than 99.5%, and is a large aggregate formed by "connecting" and growing together fine particles with a particle size range of 0.5 to 13 μm; the electrolytic titanium particles are compression molded to obtain a blank; the blank is sintered at a high temperature in an atmosphere protection furnace to obtain bimodal pore size porous titanium.
[0031] The present invention molds the particles with a particle size of 74 to 833 μm to obtain a blank. In the present invention, the pressure of the molding is 50 to 190 MPa; in a specific embodiment, the pressure of the molding is 50 MPa, 110 MPa or 190 MPa. The holding time of the molding is 4 to 6 minutes, preferably 5 minutes. In the present invention, because the electrolytic titanium powder particles are secondary particles, there are a large number of pores formed by primary particles in the particles. Therefore, during the pressing process, the source of the pores of the electrolytic titanium powder blank is not only the bridging holes of the secondary particles, but also the original pores between the primary particles of the original titanium powder. With the increase of the molding pressure, the bridging void space is compressed, and at the same time, the original pores of the primary particles of the electrolytic powder are compressed. Therefore, the molding pressure should not be controlled too high or too low; too low molding pressure is not conducive to full contact between particles and sintering; too high pressure will be too dense; that is, by controlling the molding pressure, the porosity of the final product can be regulated.
[0032] After obtaining the blank, the present invention sintered the blank to obtain porous titanium. The sintering atmosphere in the present invention is an argon atmosphere. The sintering in the present invention is a reduced pressure sintering with an absolute pressure of less than 1Pa; in a specific embodiment, a reduced pressure sintering with an absolute pressure of 0.9Pa is used.
[0033] The present invention uses pure titanium obtained by molten salt electrolysis as raw material, and directly prepares porous titanium by compression molding-sintering, avoiding the cumbersome steps of pore-forming agent filling and molding and then removing the pore-forming agent, greatly shortening the process. On the other hand, the electrolytic titanium used is a large aggregate formed by "connecting" and growing together fine particles with a particle size range of 0.5 to 13 μm in microscopic morphology. Particles of a certain particle size are obtained by crushing and screening. The particles themselves are porous. When compression molding is performed, the bridges between the particles can form a large pore space with a larger pore size. Combined with the particles themselves having a smaller pore size, the prepared porous titanium has a bimodal pore size distribution and a higher porosity; while the porous titanium prepared by direct compression molding of solid particle powders such as hydrogenation dehydrogenation or spherical titanium powder has only bridging holes between particles, and can only obtain porous titanium with a single-peak pore size distribution. The porous titanium obtained under the same preparation conditions has a lower porosity. Furthermore, the porosity can be regulated by selective control of the molding pressure and sintering conditions.
[0034] The sintering temperature of the present invention is 950-1300°C. As the sintering temperature increases, the speed of atomic diffusion will be accelerated, the active atoms on the contact surface between particles will be increased, and a bonding surface will be formed. As the bonding surface between particles expands, a sintering neck will be formed. The pores between the powder particles will gradually become smaller, especially the bridging holes between the secondary particles will also decrease as the sintering proceeds. When the temperature is above 1300°C, over-sintering will occur, and dense areas will appear locally. Therefore, controlling the sintering temperature within the above range is conducive to obtaining a better sintering effect and pore structure. The sintering temperature is preferably 950-1200°C. In a specific embodiment of the present invention, the sintering temperatures are 950°C, 1100°C and 1200°C. The holding time is 110-130min, preferably 2h.
[0035] The sintering in the present invention is reduced pressure sintering, preferably reduced pressure sintering with a pressure less than 1 Pa; preferably, the sintering is performed in an argon atmosphere.
[0036] Figure 1 The present invention discloses a method for preparing bimodal porous titanium using electrolytic titanium, which comprises: physically crushing and screening the electrolytic titanium to obtain electrolytic titanium particles; the electrolytic titanium is pure titanium with a purity greater than 99.5%, and is a large aggregate formed by "connecting" and growing together fine particles with a particle size range of 0.5 to 13 μm; the electrolytic titanium particles are compression molded to obtain a blank; and the blank is sintered at a high temperature in an atmosphere protection furnace to obtain bimodal porous titanium.
[0037] In order to further illustrate the present invention, a method for preparing porous titanium using electrolytic pure titanium as a raw material provided by the present invention is described in detail below in conjunction with embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0038] Example 1
[0039] Take electrolytic titanium with a Ti content greater than 99.7%, use a shear crusher under argon atmosphere to crush the electrolytic titanium into electrolytic titanium particles, and then screen them to select electrolytic titanium particles with a particle size of 365 to 833 μm (see Figure 2 The samples (a) to (c)) were loaded into a steel mold and pressure-molded at a molding pressure of 110 MPa. The pressure was maintained for 5 minutes. After the pressure was slowly released, the samples were sintered under reduced pressure at 1100°C and an absolute pressure of 0.9 Pa in a closed atmosphere protection furnace using an argon atmosphere for 2 hours. The samples were taken out after being cooled in the furnace. The tested porosity was 54.2%. The pore size distribution of the samples had a bimodal characteristic distribution as measured by a mercury intrusion instrument. Figure 3 It is shown that there are two peak distributions in the pore size ranges of 1.4-8.1 μm and 10.2-107.3 μm respectively.
[0040] Figure 2 As can be seen in (b), the particles with a particle size of 74 to 833 μm are aggregates formed by the connection and growth of fine particles with a particle size range of 0.5 to 13 μm, and have pores with a pore size range of 1 to 8 μm.
[0041] Example 2
[0042] Take electrolytic titanium with a Ti content of 99.7%, use a shear crusher under argon atmosphere to crush the electrolytic titanium into electrolytic titanium particles, and then screen them to select electrolytic titanium particles with a particle size of 74 to 104 μm (see Figure 2 The samples (d) to (f)) were loaded into a steel mold and pressure-formed at a molding pressure of 190 MPa. The pressure was maintained for 5 minutes. After slowly releasing the pressure, the samples were sintered at 1200°C and an absolute pressure of 0.9 Pa in a closed atmosphere protection furnace for 2 hours. The samples were cooled in the furnace and taken out. The tested porosity was 36.6%. The mercury intrusion test showed that the pore size distribution had a bimodal characteristic distribution, with bimodal distribution in the two pore size ranges of 1.2 to 8.2 μm and 10.1 to 14.8 μm, respectively.
[0043] Example 3
[0044] Take electrolytic titanium with a Ti content greater than 99.7%, use a shear crusher under argon atmosphere protection to crush the electrolytic titanium into electrolytic titanium particles, then screen, select electrolytic titanium particles with a particle size of 365-833μm and load them into a steel mold, use a molding pressure of 50MPa for pressure molding, hold the pressure for 5 minutes, slowly release the pressure, and sinter under reduced pressure at 950℃ argon atmosphere protection and an absolute pressure of 0.9Pa in a closed atmosphere protection furnace for 2h. After cooling in the furnace, take out and the tested porosity is 65%. The pore size distribution tested by a mercury intrusion meter has a bimodal characteristic distribution, with bimodal distribution in two pore size segments of 1.8-9.2μm and 14.1-202.5μm, respectively.
[0045] Comparative Example
[0046] Take hydrogenated dehydrogenated titanium powder with a Ti content of 99.5%, select electrolytic titanium particles with a particle size of 74 to 104 μm after screening, load them into a steel mold, use a molding pressure of 190 MPa for pressure molding, maintain the pressure for 5 minutes, slowly release the pressure, use 1200 ° C and an absolute pressure of 0.9 Pa in a closed atmosphere protection furnace for reduced pressure sintering, take it out after cooling with the furnace, and the porosity is tested to be 17.3%. The pore size distribution is tested by a mercury intrusion instrument. It has only one pore size peak distribution in the 10.2 to 16.4 μm particle size segment. Compared with Example 2, under the same preparation conditions, the porous titanium prepared by hydrogenated dehydrogenated titanium powder without using a pore-forming agent has a significantly lower porosity than electrolytic titanium, and the pore size distribution also has only a single peak pore size distribution.
[0047] It can be seen from the above embodiments that the present invention provides a method for preparing porous titanium using electrolytic pure titanium as raw material, comprising the following steps: crushing the electrolytic titanium and then screening it to obtain particles with a particle size of 74 to 833 μm; molding the particles with a particle size of 74 to 833 μm to obtain a blank; sintering the blank to obtain porous titanium. The present invention uses metallic pure titanium obtained by molten salt electrolysis as raw material, and directly prepares porous titanium by molding-sintering, avoiding the cumbersome steps of filling and molding with a pore-forming agent and then removing the pore-forming agent, greatly shortening the process; when the particles with a particle size of 74 to 833 μm are molded, the bridges between the particles can form a large pore space with a larger pore size, and the particles with a particle size of 74 to 833 μm are aggregates formed by connecting and growing together fine particles with a particle size range of 0.5 to 13 μm, which themselves have pores with a pore size range of 1 to 8 μm, and the prepared porous titanium has a bimodal pore size distribution and a high porosity. Experimental results show that the porous titanium prepared by the method provided by the present invention has a bimodal distribution and a porosity of 36-65%.
[0048] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing porous titanium using electrolytic pure titanium as raw material, comprising the following steps: The electrolytic titanium is crushed and sieved to obtain particles with a particle size of 74 to 833 μm; Pressing the particles with a particle size of 74 to 833 μm into a blank; The blank is sintered to obtain porous titanium.
2. The method according to claim 1, characterized in that The compression molding pressure is 50-190 MPa.
3. The method according to claim 1, characterized in that The sintering temperature is 950-1300°C.
4. The method according to claim 1, characterized in that The sintering is performed in an argon atmosphere.
5. The method according to claim 1, characterized in that The sintering adopts reduced pressure sintering with an absolute pressure less than 1Pa.
6. The method according to claim 1, characterized in that The electrolytic titanium has a purity greater than 99% and is an aggregate formed by fine particles with a particle size ranging from 0.5 to 13 μm connected and grown together.
7. The method according to claim 1, characterized in that The porous titanium has a bimodal pore size distribution.